FAKTOR RISIKO YANG BERHUBUNGAN DENGAN MORTALITAS PASCAOPERASI DARURAT PADA PASIEN AKUT ABDOMEN - , Damianus Hipolitus ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Postoperative mortality is death by any cause that occurred within 30 days postoperatively. Emergency operating procedures are generally associated with high morbidity and mortality with incidence that varies on each centers. The cause of high mortality risk is influenced by many factors and can not be fully explained. Purpose. This study aimed to determine the incidence of postoperative mortality of patients whose acute abdominal emergency surgery, to determine what the risk factors that cause mortality as well as to determine the relationship of these factors to the high risk of postoperative mortality. Method. Case - control study on 370 patients of acute abdominal emergency surgery. Acute appendicitis is the largest case emergency surgery is done 192 patients (59.89%), followed by bowel obstruction 73 patients (19.72%), perforation of hollow viscus organ 58 patients (15.67%), incarcerated hernia 33 patients (8.91% ) and other 14 patients (3.78%). Risk factors (gender, age, onset, malignancy, sepsis, comorbidities, ASA score, number of leucocytes, albumin, urea levels, creatinine levels, blood sugar level, and duration of operation) affecting the mortality was analyzed by bivariate analysis using test Chi-square and logistic regression and multivariate analysis using multilevel logistic regression . Results. Of the 370 patients who underwent emergency surgery mortality obtained by 45 patients (12.16%). The highest frequency of mortality was found in the case of a perforation of hollow viscus as many as 22 cases (48.89%) followed by bowel obstruction 14 cases (31.11%), incarcerated hernia (6.67%) and other causes (13.33%). Gastric perforation suturing procedure is a procedure that is experiencing the highest mortality of as many as 14 cases (31.11%) and followed by intestinal anastomosis 13 cases (28.89%), enterostomy (20%), hernia repair (6.67%) and other other (13.33%). With the chi square test and logistic regression showed that the risk factors affecting mortality were age, malignancy, sepsis, ASA scores, number of leukocytes, levels of urea, creatinine levels and duration of operation . With multilevel logistic regression, it was found that the most influential factor is significant malignancy (p = 0.02) and sepsis (p = 0.01) . Conclusion. Postoperative mortality in acute abdominal emergency is at 12.16%. Risk factors for mortality were age, malignancy, sepsis, ASA scores, number of leukocytes, levels of urea, creatinine levels and duration of operation. Malignancy and sepsis are risk factors that most influence the occurrence of mortality.